Antioxidant activity and sensory characteristics of Maillard reaction products derived from different peptide fractions of soybean meal hydrolysate. (15th March 2018) - Yu, Min; He, Shudong; Tang, Mingming; Zhang, Zuoyong; Zhu, Yongsheng; Sun, Hanju
Highlights: Four peptide fractions were isolated from soybean hydrolysate by ultrafiltration. 1–3 ;kDa peptides showed the highest antioxidant activity. Better sensory properties were obtained from MRPs derived from 1-3 ;kDa peptides. Low MW of raw peptides may improve flavor and antioxidant activity of MRPs. Abstract: Four peptide fractions PF1 (>5 ;kDa), PF2 (3–5 ;kDa), PF3 (1–3 ;kDa), PF4 (<1 ;kDa) were isolated from soybean hydrolysate using the ultrafiltration method. Then, d -xylose andl -cysteine were reacted with specific peptide solution at 120 ;°C for 2 ;h, and the molecular weight distribution (MWD), pH, colour, browning intensity, DPPH radical-scavenging activity, free amino acids and sensory characteristics of corresponding Maillard reaction products (MRPF1, MRPF2, MRPF3 and MRPF4) were evaluated, respectively. Peptides with low molecular weight showed higher contribution to the changes of pH, colour and browning intensity during Maillard reaction. The DPPH radical-scavenging activity of PF4 was significantly improved after Maillard reaction. Aroma volatiles and PLSR analysis suggested MRPF3 had the best sensory characteristics with higher contents of umami amino acids and lower of bitter amino acids, therefore it could be deduced that the umami and meaty characteristics were correlated with the peptides of 1–3 ;kDa.